Highly active and stable IrO2 and IrO2–Ta2O5 catalysts for oxygen evolution reaction - Li, Huibin; Pan, Yinzhi; Wu, Lei; He, Rui; Qin, Zirong; Luo, Shasha; Yang, Lijun; Zeng, Jianhuang (International journal of hydrogen energy, 2023)
The oxygen evolution reaction (OER) performance of nanosized iridium oxide-nanosheet-like based electrocatalysts synthesized by a modified Adams method is reported in this work. Cysteamine hydrochloride was introduced during the synthesis of IrO2 to induce the evolution of nanosheet-like morphology from spherical particles. The IrO2 crystallinity prepared by the modified Adams method was greatly affected by calcination temperature. When the temperature increases to 400 °C, the resulted iridium oxide transitions from pseudo-amorphous to crystal rutile type. Electrochemical evaluation results show that the IrO2 synthesized at 400 °C performs the best in terms of enhanced mass activity (1.104 A mg−1@1.6 V) and lower overpotential (315 mV@10 mA cm−2) as compared with the counterparts prepared at other temperatures. Ta2O5 with different molar ratios of Ir/Ta was incorporated to further improve the stability of iridium oxide and to reduce its usage as anode catalyst. Ultrathin IrO2–Ta2O5 nanosheets with optimized Ir/Ta = 7: 3 M ratio outperform the commercial IrO2 benchmark in terms of OER activity and stability. The overpotential of IrO2–Ta2O5(7: 3) is at 326 mV@10 mA cm−2, and its mass activity is as high as 0.9 A mg−1@1.6 V. Chronopotentiometry and chronoamperometry tests verify its excellent durability. •Amorphous IrO2 and IrO2–Ta2O5 were synthesized by modified Adams method.•IrO2–Ta2O5(7: 3) shows OER activity of 0.9 A mg−1 and overpotential of 326 mV@10 mA cm−2.•IrO2–Ta2O5(7: 3) also exhibits excellent stability.